Joint Channel and Impulsive Noise Estimation in Underwater Acoustic OFDM Systems - Chen, P.; Rong, Y.; Nordholm, Sven; He, Z. (Institute of Electrical and Electronics Engineers, 2017)
IEEE Impulsive noise is one key factor that limits the performance of underwater acoustic (UA) communications. In this paper, two pilot-subcarrier based algorithms are proposed to improve the performance of channel estimation and impulsive noise mitigation for UA orthogonal frequency-division multiplexing (OFDM) systems. The first algorithm jointly estimates the channel and the impulsive noise based on the least-squares (LS) principle. The second algorithm is developed with the aim to reduce the computational complexity, where the expectation-maximization (EM) principle is applied to estimate the channel and the impulsive noise iteratively. We compare the proposed algorithms by simulations and apply them to process the data collected during an experiment conducted in December 2015 in the estuary of the Swan River, Western Australia. The results show that both proposed algorithms have better performance than existing methods in mitigating impulsive noise in UA OFDM systems.